A low-carbon cement-based composition for bridge repair based on waste ceramic and a preparation method thereof

CN121913737BActive Publication Date: 2026-11-03JSTI GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610146177.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-02-02
Publication Date
2026-11-03
Estimated Expiration
2046-02-02

AI Technical Summary

Technical Problem

Existing bridge repair materials suffer from poor interfacial bonding performance, easy delayed cracking, high carbon emissions, and insufficient utilization of waste ceramic resources, making it difficult to meet the requirements of high durability and low carbon emissions in bridge repair.

Method used

By classifying and utilizing waste ceramics, introducing mineral admixtures to replace cementitious materials, and employing surface activation and in-situ seed induction treatment to construct a gradient interface structure, the porous structure of ceramic coarse aggregate is used in conjunction with shrinkage compensation components to achieve synergistic regulation of the hydration process.

Benefits of technology

It improves the interfacial bonding between cement matrix and waste ceramics, reduces carbon emissions of materials, meets the durability requirements of bridge repair, and effectively regulates the volume change of the hydration process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121913737B_ABST
    Figure CN121913737B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of low-carbon building material preparation, and provides a low-carbon cement-based composition for bridge repair based on waste ceramic and a preparation method thereof.The cement-based composition takes cement as a main cementitious material, introduces slag powder, waste ceramic powder and silica fume to form a multi-scale composite cementitious system, and cooperates with light-burned magnesium oxide to compensate for shrinkage components to realize volume stability regulation; the waste ceramic resources are recycled into fine aggregate and coarse aggregate, and surface activation and silicate-calcium source in-situ nucleation treatment are implemented on the waste ceramic coarse aggregate to construct a C-(A)-S-H crystal seed induction layer on the surface, and through pre-wetting treatment, internal curing regulation is realized, which cooperates with the shrinkage compensation components to improve the late volume stability and durability of the material; the composition realizes solid waste resource utilization and mineral admixture partial replacement of cementitious material sources, and is suitable for bridge repair and similar engineering scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of low-carbon building material preparation technology, and relates to a low-carbon cement-based composition for bridge repair based on waste ceramics and its preparation method. Background Technology

[0002] As crucial transportation infrastructure, bridges are susceptible to damage from traffic loads, environmental erosion, and temperature and humidity fluctuations during long-term service. Localized areas such as the bridge deck pavement, hinge joints, wet joints, and repaired areas are prone to cracking, spalling, and interface deterioration. To address these issues, cement-based repair materials are commonly used for localized repairs or reinforcement. However, existing cement-based bridge repair materials still have several technical shortcomings in practical applications, and the current "dual carbon" environment places higher demands on the low-carbon and solid waste resource utilization of repair materials.

[0003] On the one hand, traditional repair materials mostly use natural aggregates as the main filler component. Their surface structure is dense and chemically inert, relying primarily on physical interlocking to form an interface bond with the cement matrix. The loose structure of the interface transition zone makes it prone to crack initiation and propagation, resulting in insufficient bonding performance and long-term durability between new and old concrete to meet the requirements of bridge repair. On the other hand, bridge repair projects typically use low water-cement ratio mixes to meet early strength and workability requirements, but this leads to significant self-shrinkage and drying shrinkage issues. Existing expansion control methods often fail to be fully effective under later water-deficient conditions, increasing the risk of delayed cracking in the repair layer. Furthermore, traditional repair materials are highly dependent on cement usage, making it difficult to address the carbon emission issues in raw material acquisition and production processes while simultaneously meeting the development needs of low-carbon building materials. In addition, with the continuous increase in construction solid waste emissions, the resource utilization of recalcitrant solid waste such as waste ceramics is becoming increasingly prominent. Existing research on the application of waste ceramics in cement-based materials mainly focuses on using them simply as inert aggregates or low-activity fillers, failing to fully explore the potential value of their porous structure and silicate components in interface regulation and hydration control. In particular, there is a lack of systematic solutions for high-durability scenarios such as bridge repair, as well as a lack of low-carbon cement-based repair material technology pathways that synergistically couple mineral admixture replacement, solid waste aggregate utilization, and volume stability control. Summary of the Invention

[0004] To address the shortcomings of existing technologies, the present invention aims to provide a low-carbon cement-based composition for bridge repair based on waste ceramics and its preparation method. This method involves the graded utilization of waste ceramics and the introduction of mineral admixtures to partially replace the cementitious material source, thereby reducing the material system's dependence on cement. Furthermore, the coarse aggregate of the waste ceramics undergoes surface activation and in-situ seeding treatment to construct an interface structure with gradient characteristics on its surface, thus improving the interfacial bonding between it and the cement matrix. Simultaneously, the porous structure of the coarse aggregate of the waste ceramics, combined with shrinkage-compensating components, enables synergistic regulation of the hydration process, thereby meeting the needs of actual production.

[0005] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a low-carbon cement-based composition for bridge repair based on waste ceramics, characterized in that the composition comprises cementitious materials, fine aggregates, coarse aggregates, admixtures, shrinkage compensation components and fiber reinforcement components; The fine aggregate includes natural sand and waste ceramic sand, with the waste ceramic sand replacing 10-60% of the fine aggregate by mass; the coarse aggregate includes natural crushed stone and waste ceramic coarse aggregate, with the waste ceramic coarse aggregate replacing 10-40% of the coarse aggregate by mass; the admixture includes at least a polycarboxylate-based water-reducing agent and a viscosity modifier; the fiber reinforcement component is basalt fiber and / or polyvinyl alcohol fiber, with an admixture dosage of 0.05-0.15 vol.% based on the total volume of the composition; the waste ceramic coarse aggregate has a nano-C-(A)-SH seed crystal induction layer constructed in situ through surface activation treatment; the internal pore structure of the waste ceramic coarse aggregate can reach a saturated surface-dry state through pre-wetting treatment.

[0006] Preferably, the particle size of the waste ceramic powder meets the requirement of D50 of 8-15μm, and ≥95% passes through a 75μm sieve.

[0007] Preferably, the particle size of the waste ceramic sand is 0.15-5mm, and the particle size of the waste ceramic coarse aggregate is 5-16mm.

[0008] Preferably, the water-cement ratio of the composition after mixing with water is 0.28-0.36; the amount of the polycarboxylate superplasticizer is 0.8-1.6 wt.% based on the total mass of the cementitious materials; the amount of the viscosity modifier is 0.05-0.30 wt.% based on the total mass of the cementitious materials, and the cementitious materials, based on the total mass of the cementitious materials, include: 55-75 wt.% cement, 10-25 wt.% slag powder, 5-20 wt.% waste ceramic powder, and 2-6 wt.% silica fume; the shrinkage compensation component is a light-burned magnesium oxide expanding agent, and is 2-6 wt.% based on the total mass of the cementitious materials.

[0009] Preferably, the surface activation treatment of the waste ceramic coarse aggregate includes: alkaline etching to remove glaze / coarsen, and silicate-calcium source in-situ nucleation treatment, wherein the silicate-calcium source in-situ nucleation treatment is to nucleate the waste ceramic coarse aggregate using a silicate-containing nucleation solution.

[0010] Preferably, during the construction of the nano C-(A)-SH seed induction layer, an aluminum source modifier is further introduced. The aluminum source modifier is selected from one or more of nano alumina, nano aluminum hydroxide, or aluminum sol. The amount of the aluminum source modifier relative to the total mass of the nucleating liquid is 0.02-0.10 wt., calculated as alumina.

[0011] Secondly, the present invention provides a method for preparing a low-carbon cement-based composition for bridge repair based on waste ceramics, the method comprising: S1. Grading and preparation of waste ceramics: After cleaning and drying, waste ceramics are crushed and screened to obtain waste ceramic sand, waste ceramic coarse aggregate and waste ceramic fine material. The waste ceramic fine material is then ball-milled to obtain waste ceramic powder. S2. Surface activation and seeding induction of waste ceramic coarse aggregate, including the following steps: A1. Soak waste ceramic coarse aggregate in sodium hydroxide solution; A2, the waste ceramic coarse aggregate treated by A1 is added to the silicate-containing nucleating solution for nucleation treatment. Calcium ions and silicate ions react in situ on the surface and pores of the ceramic coarse aggregate to generate a nano C-(A)-SH seed induction layer. The nucleating solution includes water glass dilution solution and calcium hydroxide. A3, the waste ceramic coarse aggregate after nucleation treatment is pre-wetted to make it reach the saturated surface dry (SSD) state. S3. Mixing: Dry mix cement, slag powder, waste ceramic powder, silica fume and lightly calcined magnesium oxide expansion agent, then add fine aggregate and coarse aggregate and dry mix, then add mixing water containing polycarboxylate superplasticizer and viscosity modifier for wet mixing, and finally add fiber reinforcement component and disperse at low speed to obtain a low-carbon cement-based composition for bridge repair based on waste ceramics.

[0012] Preferably, in step S1, the ball-to-material ratio for preparing waste ceramic powder by ball milling is (6-10):1, the ball milling time is 60-150 min, and the shell temperature is controlled to be ≤60℃ during the ball milling process.

[0013] Preferably, the sodium hydroxide solution in A1 has a mass fraction of 0.5-2 wt.%, the soaking temperature is 40-60℃, the soaking time is 10-30 min, and the solution is rinsed until the pH of the washing solution is 7-9.

[0014] Preferably, the effective solid content of the water glass diluent in A2 is 2.0-4.0 wt.%, the amount of calcium hydroxide is 0.2-0.6 wt.% relative to the total mass of the nucleating solution, the nucleation treatment time is 8-12 min, and after treatment, it is air-dried at 35-45℃ for 1-2 h.

[0015] Preferably, the pre-wetting treatment in A3 includes soaking in water for 10-14 hours, draining for 30-45 minutes, and spreading for 8-15 minutes until there is no visible water on the surface to obtain a saturated surface-dry state. The waste ceramic coarse aggregate that has obtained the saturated surface-dry state is put into step S3 within 2 hours.

[0016] In this cement-based composition, waste ceramic materials participate in the chemical reactions and structural evolution of the cement system at different particle size scales. Under mechanical force, the surface silica-oxygen network structure of the ball-milled waste ceramic powder undergoes distortion, with some silica-oxygen bonds breaking and forming unsaturated coordination states, placing the ceramic powder surface in a thermodynamically unstable state. When dispersed in cement paste, in a strongly alkaline porous solution environment, the active silica-oxygen structure on the ceramic powder surface reacts with calcium ions in the solution, gradually forming a gel phase dominated by calcium silicate hydrates. This process is accompanied by the consumption of calcium hydroxide, causing the solid phase composition in the hydration system to evolve.

[0017] During the alkaline etching process, the original glaze layer and dense surface phase of waste ceramic coarse aggregate are dissolved and removed, exposing the silicate structure inside the ceramic matrix. Under the action of the alkaline medium, local silicon-oxygen bonds on the ceramic surface break, forming negatively charged silicon-oxygen structural units, providing sites for subsequent adsorption and binding of calcium ions. Under the coexistence of silicate and calcium source, calcium ions in the solution first accumulate on the ceramic surface and undergo condensation reactions with silicate ions, generating primary calcium silicate or calcium aluminosilicate hydrates on the ceramic surface and at its pores. These hydrates are generated in situ in solid form, with their crystal nuclei connected to the ceramic matrix by chemical bonding, and expanding along the microscopic undulations and pore structure of the ceramic surface.

[0018] Because of the open pores on and near the surface of ceramic coarse aggregate, the in-situ generated hydration seeds are not only distributed on the outer surface but also extend into the pores, forming a continuous solid-phase transition region. During subsequent cement hydration, calcium ions and silicate ions generated from the dissolution of cement particles undergo heterogeneous nucleation reactions on these pre-existing seed surfaces, causing hydration products to preferentially deposit and grow in this region. This process alters the formation pathway of hydration products at the interface, making solid-phase formation at the interface no longer solely dependent on the random deposition of cement particles but controlled by the existing seed structure.

[0019] Simultaneously, the pores within the waste ceramic coarse aggregate are filled with water under pre-wetting conditions. As the cement hydration reaction continues, the water in the matrix pore solution is consumed, creating a water chemical potential difference between the interior and exterior of the ceramic aggregate. Pore water migrates along the pore channels into the matrix. This migration process keeps the interface and its adjacent areas in an environment conducive to hydration reactions, providing the necessary conditions for silicate hydration and magnesium-containing component hydration reactions. Thus, the hydration reaction at the interface, the seed-induced reaction, and the hydration process within the matrix occur continuously in time and space.

[0020] As a preferred technical solution of the present invention, in S1, the ball-to-material ratio for preparing waste ceramic powder by ball milling in S1 is (6-10):1, the ball milling time is 60-150 min, and the shell temperature is controlled ≤60℃ during the ball milling process. For example, the ball-to-material ratio can be (6, 6.4, 6.8, 7.2, 7.6, 8, 8.4, 8.8, 9.2, 9.6 or 10):1, the ball milling time is (60, 69, 78, 87, 96, 105, 114, 123, 132, 141 or 150) min, and the shell temperature is controlled ≤60℃ during the ball milling process. However, it is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0021] As a preferred embodiment of the present invention, in S2, the effective solid content of the water glass diluent in A2 is 2.0-4.0 wt.%, the amount of calcium hydroxide used is 0.2-0.6 wt.% relative to the total mass of the nucleating solution, the nucleation treatment time is 8-12 min, and after treatment, it is air-dried at 35-45℃ for 1-2 h. For example, the effective solid content of the water glass diluent can be (2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8% or 4.0%) wt.%, and the amount of calcium hydroxide used is (0.2%, 0.24%, 0.28%, 0.24%) relative to the total mass of the nucleating solution. The nucleation treatment time is (8.0, 8.4, 8.8, 9.2, 9.6, 10.0, 10.4, 10.8, 11.2, 11.6 or 12.0) min, and then air-dried at (35, 36, 37, 38, 39, 40, 41, 42, 43, 44 or 45) °C for (1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0) h, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0022] In some optional embodiments, the pre-wetting treatment of A3 includes soaking in water for 10-14 hours, draining for 30-45 minutes, and spreading for 8-15 minutes until there is no visible water on the surface to obtain a saturated surface-dry state. The waste ceramic coarse aggregate that has obtained the saturated surface-dry state is put into step S3 within 2 hours. For example, it can be: soaking in water for (10.0, 10.4, 10.8, 11.2, 11.6, 12.0, 12.4, 12.8, 13.2, 13.6 or 14.0) hours, draining for (30, 31) hours. 5, 33, 34.5, 36, 37.5, 39, 40.5, 42, 43.5 or 45 min and spread for (8.0, 8.7, 9.4, 10.1, 10.8, 11.5, 12.2, 12.9, 13.6, 14.3 or 15.0) min until there is no visible water on the surface to obtain a saturated surface-dry state. The waste ceramic coarse aggregate that has obtained the saturated surface-dry state shall be put into step S3 within 2 hours, but it is not limited to the listed values. Other unlisted values ​​within the range of values ​​are also applicable.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention utilizes waste ceramics in a graded manner and performs surface activation treatment on waste ceramic coarse aggregates to construct a hydration seed induction layer in situ on the surface of ceramic aggregates, so that cement hydration products are continuously generated in the aggregate interface region, thereby improving the structural composition of the interface transition zone; the pore structure inside the waste ceramic coarse aggregates participates in the hydration process regulation under pre-wetting conditions, providing continuous water supply to the system, so that the relevant hydration reactions can be carried out synergistically at the interface and inside the matrix; at the same time, the shrinkage compensation component and the internal curing process work together to regulate the volume change of the cement-based system during the hardening process, and achieves the low-carbon composition of the cementitious system through the synergistic substitution of mineral admixtures and waste ceramic powder; by introducing waste ceramic powder to participate in the cementitious system reaction, the solid phase structure in the cement matrix gradually evolves and tends to be dense. Attached Figure Description

[0024] Figure 1 This is a SEM image of the interface between waste ceramic coarse aggregate and cement matrix provided in Embodiment 1 of the present invention; Figure 2 This is a SEM image of the molded repair material provided in Embodiment 1 of the present invention; Figure 3 This is a mixing photograph of the low-carbon cement-based composition for bridge repair based on waste ceramics provided in Embodiment 1 of the present invention; Figure 4 Photographs of standard specimens of the mixed cement-based composition provided by this invention. Detailed Implementation

[0025] The technical solutions of the present invention will be described in detail below with reference to specific embodiments and accompanying drawings. The embodiments described herein are specific implementations of the present invention, used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary, and should not be construed as limiting the implementation methods or the scope of protection of the present invention. In addition to the embodiments described herein, those skilled in the art can employ other obvious technical solutions based on the content disclosed in the claims and specification of this application. These technical solutions include those that make any obvious substitutions and modifications to the embodiments described herein.

[0026] The chemical reagents used in the embodiments and comparative examples of this invention are all commercially available products and have not undergone any further purification treatment.

[0027] Example 1 This embodiment provides a low-carbon cement-based composition for bridge repair based on waste ceramics and its preparation method, specifically including: A low-carbon cement-based composition for bridge repair based on waste ceramics, the composition comprising cementitious materials, fine aggregates, coarse aggregates, admixtures, shrinkage compensation components, and fiber reinforcement components; The cementitious material, by total mass, comprises: 55 wt.% cement, 25 wt.% slag powder, 5 wt.% waste ceramic powder, and 6 wt.% silica fume. The shrinkage compensation component is a lightly calcined magnesium oxide expanding agent, comprising 2 wt.% of the total mass of the cementitious material. The fine aggregate includes natural sand and waste ceramic sand, with waste ceramic sand replacing 60% of the fine aggregate by mass; the coarse aggregate includes natural crushed stone and waste ceramic coarse aggregate, with waste ceramic coarse aggregate replacing 10% of the coarse aggregate by mass. The fiber reinforcement component is basalt fiber, and its dosage is 0.15 vol.% based on the total volume of the composition. The water-cement ratio of the composition after mixing with water is 0.28; the amount of the polycarboxylate superplasticizer is 1.6 wt.% based on the total mass of the cementitious materials; the amount of the viscosity modifier is 0.05 wt.% based on the total mass of the cementitious materials. During the construction of the nano-C-(A)-SH seed induction layer, an aluminum source modifier is further introduced. The aluminum source modifier is selected from nano-alumina, and its dosage, based on alumina, is 0.10 wt.% relative to the total mass of the nucleation solution. A method for preparing a low-carbon cement-based composition for bridge repair based on waste ceramics includes: S1. After cleaning and drying, the waste ceramics are crushed and screened to obtain waste ceramic sand, waste ceramic coarse aggregate and waste ceramic fine material. The waste ceramic fine material is ball-milled to obtain waste ceramic powder with a particle size D50 of 15μm. The ball-to-material ratio for ball milling waste ceramic powder is 6:1, the ball milling time is 150min, and the shell temperature is controlled ≤60℃ during the ball milling process. S2. Surface activation and seeding induction of waste ceramic coarse aggregate, including the following steps: A1. Place the waste ceramic coarse aggregate in a 0.5 wt.% sodium hydroxide solution, soak it at 60°C for 10 min, and then rinse until the pH of the washing solution is 7. A2, the waste ceramic coarse aggregate treated in A1 is brought into contact with a silicate-containing nucleating solution, wherein the effective solid content of the water glass dilution in the nucleating solution is 4.0 wt.%, the amount of calcium hydroxide is 0.2 wt.% relative to the total mass of the nucleating solution, the nucleation treatment time is 12 min, and after treatment, it is air-dried at 35°C for 2 h; A3, the waste ceramic coarse aggregate after nucleation treatment is pre-wetted, including soaking in water for 14 hours, draining for 30 minutes and spreading for 15 minutes until there is no visible water on the surface to obtain a saturated surface dry state, and then put into step S3 within 2 hours. S3. Mixing: Dry mix cement, slag powder, waste ceramic powder, silica fume and lightly calcined magnesium oxide expansion agent, then add fine aggregate and coarse aggregate and dry mix, then add mixing water containing polycarboxylate superplasticizer and viscosity modifier for wet mixing, and finally add fiber reinforcement component and disperse at low speed to obtain a low-carbon cement-based composition for bridge repair based on waste ceramics.

[0028] Figure 1 This is a SEM image of the interface between waste ceramic coarse aggregate and cement matrix provided in this embodiment. A densified deposition zone can be seen at the interface. The ceramic side has a porous and rough morphology, while the matrix side has a hydration product accumulation structure. Figure 2 This is a SEM image of the molded repair material provided in this embodiment; Figure 3 This is a mixing photograph of the low-carbon cement-based composition for bridge repair based on waste ceramics provided in Embodiment 1 of the present invention; Figure 4 Photographs of standard specimens of the mixed cement-based composition provided in this embodiment.

[0029] Example 2 This embodiment provides a low-carbon cement-based composition for bridge repair based on waste ceramics and its preparation method, specifically including: A low-carbon cement-based composition for bridge repair based on waste ceramics, the composition comprising cementitious materials, fine aggregates, coarse aggregates, admixtures, shrinkage compensation components, and fiber reinforcement components; The cementitious material, by total mass, comprises: 75 wt.% cement, 10 wt.% slag powder, 20 wt.% waste ceramic powder, and 2 wt.% silica fume. The compensating shrinkage component is a lightly calcined magnesium oxide expanding agent, comprising 6 wt.% of the total mass of the cementitious material. The fine aggregate includes natural sand and waste ceramic sand, with waste ceramic sand replacing 10% of the fine aggregate by mass; the coarse aggregate includes natural crushed stone and waste ceramic coarse aggregate, with waste ceramic coarse aggregate replacing 40% of the coarse aggregate by mass. The fiber reinforcement component is polyvinyl alcohol fiber, and its dosage is 0.05 vol.% based on the total volume of the composition. The water-cement ratio of the composition after mixing with water is 0.36; the amount of the polycarboxylate superplasticizer is 0.8 wt.% based on the total mass of the cementitious materials; the amount of the viscosity modifier is 0.30 wt.% based on the total mass of the cementitious materials. During the construction of the nano-C-(A)-SH seed induction layer, an aluminum source modifier is further introduced. The aluminum source modifier is selected from nano-aluminum hydroxide, and its dosage, based on alumina, is 0.02 wt.% relative to the total mass of the nucleation solution. A method for preparing a low-carbon cement-based composition for bridge repair based on waste ceramics includes: S1. After cleaning and drying, the waste ceramics are crushed and screened to obtain waste ceramic sand, waste ceramic coarse aggregate and waste ceramic fine material. The waste ceramic fine material is ball-milled to obtain waste ceramic powder with a particle size D50 of 8μm. The ball-to-material ratio for ball milling waste ceramic powder is 10:1, the ball milling time is 60min, and the shell temperature is controlled ≤60℃ during the ball milling process. S2. Surface activation and seeding induction of waste ceramic coarse aggregate, including the following steps: A1. Place the waste ceramic coarse aggregate in a 2.0 wt.% sodium hydroxide solution, soak at 40°C for 30 min, and then rinse until the pH of the washing solution is 8. A2, the waste ceramic coarse aggregate treated in A1 is contacted with a silicate-containing nucleating solution, wherein the effective solid content of the water glass dilution in the nucleating solution is 2.0 wt.%, the amount of calcium hydroxide is 0.6 wt.% relative to the total mass of the nucleating solution, the nucleation treatment time is 8 min, and after treatment, it is air-dried at 45℃ for 1 h; A3, the waste ceramic coarse aggregate after nucleation treatment is pre-wetted, including soaking in water for 10 hours, draining for 45 minutes and spreading for 8 minutes until there is no visible water on the surface to obtain a saturated surface dry state, and then put into step S3 within 2 hours. S3. Mixing: Dry mix cement, slag powder, waste ceramic powder, silica fume and lightly calcined magnesium oxide expansion agent, then add fine aggregate and coarse aggregate and dry mix, then add mixing water containing polycarboxylate superplasticizer and viscosity modifier for wet mixing, and finally add fiber reinforcement component and disperse at low speed to obtain a low-carbon cement-based composition for bridge repair based on waste ceramics.

[0030] Example 3 This embodiment provides a low-carbon cement-based composition for bridge repair based on waste ceramics and its preparation method, specifically including: A low-carbon cement-based composition for bridge repair based on waste ceramics, the composition comprising cementitious materials, fine aggregates, coarse aggregates, admixtures, shrinkage compensation components, and fiber reinforcement components; The cementitious material, by total mass, comprises: 65 wt.% cement, 15 wt.% slag powder, 15 wt.% waste ceramic powder, and 4 wt.% silica fume. The shrinkage compensation component is a lightly calcined magnesium oxide expanding agent, comprising 4 wt.% of the total mass of the cementitious material. The fine aggregate includes natural sand and waste ceramic sand, with waste ceramic sand replacing 40% of the fine aggregate by mass; the coarse aggregate includes natural crushed stone and waste ceramic coarse aggregate, with waste ceramic coarse aggregate replacing 25% of the coarse aggregate by mass. The fiber reinforcement component is a mixture of basalt fiber and polyvinyl alcohol fiber, with a content of 0.10 vol.% based on the total volume of the composition. The water-cement ratio of the composition after mixing with water is 0.32; the amount of the polycarboxylate superplasticizer is 1.2 wt.% based on the total mass of the cementitious materials; the amount of the viscosity modifier is 0.15 wt.% based on the total mass of the cementitious materials. During the construction of the nano-C-(A)-SH seed induction layer, an aluminum source modifier is further introduced. This aluminum source modifier is selected from aluminum sol and, based on alumina, its dosage relative to the total mass of the nucleation solution is 0.05 wt.%. A method for preparing a low-carbon cement-based composition for bridge repair based on waste ceramics includes: S1. After cleaning and drying, the waste ceramics are crushed and screened to obtain waste ceramic sand, waste ceramic coarse aggregate and waste ceramic fine material. The waste ceramic fine material is ball-milled to obtain waste ceramic powder with a particle size D50 of 12μm. The ball-to-material ratio for ball milling waste ceramic powder is 8:1, the ball milling time is 100min, and the shell temperature is controlled ≤60℃ during the ball milling process. S2. Surface activation and seeding induction of waste ceramic coarse aggregate, including the following steps: A1. Place the waste ceramic coarse aggregate in a 1.0 wt.% sodium hydroxide solution, soak it at 50°C for 20 min, and then rinse until the pH of the washing solution is 9. A2, the waste ceramic coarse aggregate treated in A1 is brought into contact with a silicate-containing nucleating solution, wherein the effective solid content of the water glass dilution in the nucleating solution is 3.0 wt.%, the amount of calcium hydroxide is 0.4 wt.% relative to the total mass of the nucleating solution, the nucleation treatment time is 10 min, and after treatment, it is air-dried at 40℃ for 1.5 h; A3, the waste ceramic coarse aggregate after nucleation treatment is pre-wetted, including soaking in water for 12 hours, draining for 40 minutes and spreading for 10 minutes until there is no visible water on the surface to obtain a saturated surface dry state, and then put into step S3 within 2 hours. S3. Mixing: Dry mix cement, slag powder, waste ceramic powder, silica fume and lightly calcined magnesium oxide expansion agent, then add fine aggregate and coarse aggregate and dry mix, then add mixing water containing polycarboxylate superplasticizer and viscosity modifier for wet mixing, and finally add fiber reinforcement component and disperse at low speed to obtain a low-carbon cement-based composition for bridge repair based on waste ceramics.

[0031] Example 4 This embodiment provides a low-carbon cement-based composition for bridge repair based on waste ceramics and its preparation method, specifically including: A low-carbon cement-based composition for bridge repair based on waste ceramics, the composition comprising cementitious materials, fine aggregates, coarse aggregates, admixtures, shrinkage compensation components, and fiber reinforcement components; The cementitious material, by total mass, comprises: 60 wt.% cement, 20 wt.% slag powder, 10 wt.% waste ceramic powder, and 5 wt.% silica fume. The shrinkage compensation component is a lightly calcined magnesium oxide expanding agent, comprising 5 wt.% of the total mass of the cementitious material. The fine aggregate includes natural sand and waste ceramic sand, with waste ceramic sand replacing 50% of the fine aggregate by mass; the coarse aggregate includes natural crushed stone and waste ceramic coarse aggregate, with waste ceramic coarse aggregate replacing 30% of the coarse aggregate by mass. The fiber reinforcement component is basalt fiber, and its dosage is 0.12 vol.% based on the total volume of the composition. The water-cement ratio of the composition after mixing with water is 0.30; the amount of the polycarboxylate superplasticizer is 1.0 wt.% based on the total mass of the cementitious materials; the amount of the viscosity modifier is 0.20 wt.% based on the total mass of the cementitious materials. During the construction of the nano-C-(A)-SH seed induction layer, an aluminum source modifier is further introduced. The aluminum source modifier is selected from a mixture of nano-alumina and aluminum sol, and its dosage, based on alumina, is 0.08 wt.% relative to the total mass of the nucleation solution. A method for preparing a low-carbon cement-based composition for bridge repair based on waste ceramics includes: S1. After cleaning and drying, the waste ceramics are crushed and screened to obtain waste ceramic sand, waste ceramic coarse aggregate and waste ceramic fine material. The waste ceramic fine material is ball-milled to obtain waste ceramic powder with a particle size D50 of 10μm. The ball-to-material ratio for ball milling waste ceramic powder is 9:1, the ball milling time is 120min, and the shell temperature is controlled ≤60℃ during the ball milling process. S2. Surface activation and seeding induction of waste ceramic coarse aggregate: A1. Place the waste ceramic coarse aggregate in a 1.5 wt.% sodium hydroxide solution, soak at 55°C for 25 min, and then rinse until the pH of the washing solution is 8.5. A2, the waste ceramic coarse aggregate treated in A1 is contacted with a silicate-containing nucleating solution, wherein the effective solid content of the water glass dilution in the nucleating solution is 2.5 wt.%, the amount of calcium hydroxide is 0.5 wt.% relative to the total mass of the nucleating solution, the nucleation treatment time is 9 min, and after treatment, it is air-dried at 42℃ for 1.2 h; A3, the waste ceramic coarse aggregate after nucleation treatment is pre-wetted, including soaking in water for 11 hours, draining for 35 minutes and spreading for 12 minutes until there is no visible water on the surface to obtain a saturated surface dry state, and then put into step S3 within 2 hours. S3. Mixing: Dry mix cement, slag powder, waste ceramic powder, silica fume and lightly calcined magnesium oxide expansion agent, then add fine aggregate and coarse aggregate and dry mix, then add mixing water containing polycarboxylate superplasticizer and viscosity modifier for wet mixing, and finally add fiber reinforcement component and disperse at low speed to obtain a low-carbon cement-based composition for bridge repair based on waste ceramics.

[0032] Comparative Example 1 This comparative example provides a low-carbon cement-based composition for bridge repair based on waste ceramics and its preparation method. The difference between this example and Example 1 is that the waste ceramic coarse aggregate is only subjected to conventional cleaning and drying treatment before use, without undergoing surface activation treatment with alkaline solution, without contact with silicate-containing nucleating liquid, and without constructing a nano-crystal seed induction layer on its surface. Other process parameters and operating conditions are exactly the same as in Example 1.

[0033] Comparative Example 2 This comparative example provides a low-carbon cement-based composition for bridge repair based on waste ceramics and its preparation method. The difference between this and Example 1 is that in the seed induction treatment of waste ceramic coarse aggregate, no aluminum source modifier is introduced into the nucleation solution. Instead, an aluminum-free calcium silicate hydrate seed layer is formed on the surface of the ceramic coarse aggregate only through silicate and calcium source. Other process parameters and operating conditions are exactly the same as in Example 1.

[0034] Comparative Example 3 This comparative example provides a low-carbon cement-based composition for bridge repair based on waste ceramics and its preparation method. The difference between this and Example 1 is that the composition does not contain lightly calcined magnesium oxide expanding agent, while other process parameters and operating conditions are exactly the same as in Example 1.

[0035] Detection method: The compressive strength was tested according to the "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" GB / T 50081, and the mixed cement-based composition was molded into standard specimens. Figure 4 As shown in the figure, the test was conducted after curing under the specified conditions for 28 days.

[0036] Splitting tensile strength was tested in accordance with the "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" GB / T 50081.

[0037] The drying shrinkage rate was tested according to the "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" GB / T 50082. After curing the molded specimens under the specified curing conditions, they were transferred to a drying environment. The change in specimen length was measured periodically, and the drying shrinkage rate was calculated based on the change in length at different ages.

[0038] Table 1 shows the test results of the molded bodies of low-carbon cement-based compositions for bridge repair based on waste ceramics in Examples 1-4 and Comparative Examples 1-3.

[0039] Table 1. Test results of molded articles of low-carbon cement-based compositions for bridge repair based on waste ceramics from Examples 1-4 and Comparative Examples 1-3. As shown in Table 1, compared with Example 1, the compressive strength of Comparative Example 1 decreased, the splitting tensile strength decreased, and the drying shrinkage rate increased; the compressive strength of Comparative Example 2 decreased, the splitting tensile strength decreased, and the drying shrinkage rate increased; and the compressive strength of Comparative Example 3 decreased, the splitting tensile strength decreased, and the drying shrinkage rate increased.

[0040] This is because, in Comparative Example 1, the waste ceramic coarse aggregate was not subjected to alkaline etching for glaze removal / coarsening and in-situ silicate-calcium source nucleation treatment. The interface lacked a seed-inducing layer, and the hydration products lacked heterogeneous nucleation sites for nucleation and growth on the ceramic surface. The interface transition zone was more prone to porosity and areas of insufficient continuity, resulting in reduced compressive strength and splitting tensile strength. Simultaneously, increased moisture migration and drying gradient at the interface led to increased drying shrinkage. In Comparative Example 2, because no aluminum source modifier was introduced into the nucleation solution, the seed crystals formed on the ceramic surface were mainly CSH, lacking C-(A)-SH components involving aluminum structural units. The interface densification and bonding were weaker than in Example 1, resulting in reduced compressive strength and splitting tensile strength. At the same time, the ability to regulate the pore structure in the interface region was weakened, making it difficult to mitigate volume changes caused by moisture migration, thus increasing drying shrinkage. In Comparative Example 3, since no lightly calcined magnesium oxide expansion agent was added, the system lacked a source of volume compensation for shrinkage strain during the hardening process. Although the ceramic coarse aggregate still had a seed-inducing layer and pre-wetting and water release could maintain hydration, shrinkage deformation was more likely to accumulate and be transformed into macroscopic drying shrinkage, resulting in a higher drying shrinkage rate than in Example 1, and a decrease in splitting tensile strength and compressive strength.

[0041] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A low-carbon cement-based composition for bridge repair based on waste ceramics, characterized in that, The composition includes cementitious materials, fine aggregates, coarse aggregates, admixtures, shrinkage compensation components, and fiber reinforcement components; The fine aggregate includes natural sand and waste ceramic sand, with the waste ceramic sand replacing 10-60% of the fine aggregate by mass; the coarse aggregate includes natural crushed stone and waste ceramic coarse aggregate, with the waste ceramic coarse aggregate replacing 10-40% of the coarse aggregate by mass; the admixture includes at least a polycarboxylate-based water-reducing agent and a viscosity modifier; the fiber reinforcement component is basalt fiber and / or polyvinyl alcohol fiber, with an admixture dosage of 0.05-0.15 vol.% based on the total volume of the composition; the waste ceramic coarse aggregate has a nano-C-(A)-SH seed crystal induction layer constructed in situ through surface activation treatment; the internal pore structure of the waste ceramic coarse aggregate can reach a saturated surface-dry state through pre-wetting treatment.

2. The low-carbon cement-based composition for bridge repair based on waste ceramics according to claim 1, characterized in that, The waste ceramic sand has a particle size of 0.15-5mm, and the waste ceramic coarse aggregate has a particle size of 5-16mm.

3. The low-carbon cement-based composition for bridge repair based on waste ceramics according to claim 1, characterized in that, The water-cement ratio of the composition after mixing with water is 0.28-0.36; the amount of the polycarboxylate superplasticizer is 0.8-1.6 wt.% based on the total mass of the cementitious materials; the amount of the viscosity modifier is 0.05-0.30 wt.% based on the total mass of the cementitious materials, and the cementitious materials include: 55-75 wt.% cement, 10-25 wt.% slag powder, 5-20 wt.% waste ceramic powder, and 2-6 wt.% silica fume based on the total mass of the cementitious materials; the shrinkage compensation component is a light-burned magnesium oxide expanding agent, which is 2-6 wt.% based on the total mass of the cementitious materials; the particle size of the waste ceramic powder meets the requirement of D50 of 8-15 μm, and ≥95% passes through a 75 μm sieve.

4. The low-carbon cement-based composition for bridge repair based on waste ceramics according to claim 1, characterized in that, The surface activation treatment of the waste ceramic coarse aggregate includes: alkaline etching to remove glaze and thicken the aggregate and silicate-calcium source in-situ nucleation treatment. The silicate-calcium source in-situ nucleation treatment is to nucleate the waste ceramic coarse aggregate using a silicate-containing nucleation solution.

5. A low-carbon cement-based composition for bridge repair based on waste ceramics according to claim 4, characterized in that, During the construction of the nano C-(A)-SH seed induction layer, an aluminum source modifier is further introduced. The aluminum source modifier is selected from one or more of nano alumina, nano aluminum hydroxide, or aluminum sol. The amount of the aluminum source modifier relative to the total mass of the nucleation liquid is 0.02-0.10 wt., calculated as alumina.

6. A method for preparing a low-carbon cement-based composition for bridge repair based on waste ceramics as described in any one of claims 1-5, characterized in that, Includes the following steps: S1. Grading and preparation of waste ceramics: After cleaning and drying, waste ceramics are crushed and screened to obtain waste ceramic sand, waste ceramic coarse aggregate and waste ceramic fine material. The waste ceramic fine material is then ball-milled to obtain waste ceramic powder. S2. Surface activation and seeding induction of waste ceramic coarse aggregate, including the following steps: A1. Soak waste ceramic coarse aggregate in sodium hydroxide solution; A2, the waste ceramic coarse aggregate treated in A1 is added to a silicate-containing nucleating solution for nucleation treatment, wherein the nucleating solution includes water glass dilution and calcium hydroxide; A3, pre-wetting treatment of waste ceramic coarse aggregate after nucleation treatment; S3. Mixing: Dry mix cement, slag powder, waste ceramic powder, silica fume and lightly calcined magnesium oxide expansion agent, then add fine aggregate and coarse aggregate and dry mix, then add mixing water containing polycarboxylate superplasticizer and viscosity modifier for wet mixing, and finally add fiber reinforcement component and disperse at low speed to obtain a low-carbon cement-based composition for bridge repair based on waste ceramics.

7. The method for preparing a low-carbon cement-based composition for bridge repair based on waste ceramics according to claim 6, characterized in that, In S1, the ball-to-material ratio for preparing waste ceramic powder by ball milling is (6-10):1, the ball milling time is 60-150 min, and the shell temperature is controlled ≤60℃ during the ball milling process.

8. The method for preparing a low-carbon cement-based composition for bridge repair based on waste ceramics according to claim 6, characterized in that, The sodium hydroxide solution in A1 has a mass fraction of 0.5-2 wt.%, the soaking temperature is 40-60℃, the soaking time is 10-30 min, and after soaking, it is rinsed until the pH of the washing solution is 7-9; The effective solid content of the water glass diluent in A2 is 2.0-4.0 wt.%, the amount of calcium hydroxide is 0.2-0.6 wt.% relative to the total mass of the nucleating solution, the nucleation treatment time is 8-12 min, and after treatment, it is air-dried at 35-45℃ for 1-2 h.

9. A method for preparing a low-carbon cement-based composition for bridge repair based on waste ceramics according to claim 6, characterized in that, The pre-wetting treatment in A3 includes soaking in water for 10-14 hours, draining for 30-45 minutes, and spreading for 8-15 minutes until there is no visible water on the surface to obtain a saturated surface-dry state. The waste ceramic coarse aggregate that has obtained the saturated surface-dry state is put into step S3 within 2 hours.

Citation Information

Patent Citations

  • High-temperature-resistant concrete based on regenerated ceramic aggregate and preparation method of high-temperature-resistant concrete

    CN112939533A

  • Low-shrinkage waste ceramic concrete suitable for hollow slab hinge joint as well as preparation method and application of low-shrinkage waste ceramic concrete

    CN121135267A